HUKUMAN DAN GANJARAN DALAM PERSPEKTIF ISLAM: RELEVANSINYA DENGAN PENDIDIKAN MORAL DI ERA MODERN - Febi Febrianda; Muhammad Fauzan; Charles (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This article discusses the concept of punishment and reward in an Islamic perspective and its relevance to today's living conditions. This study aims to review the related literature to understand the implementation of punishment and reward in education and its impact on students' moral behavior in the modern era. This type of research is included in library research which examines theoretically and in-depth a discussion so that conclusions will be obtained. The method used in this writing is a literature review, which is a collection of books or other sources related to punishment and reward in an Islamic perspective: Its Relevance to Education and Morality in the Modern Era. In this writing, various literacy sources are also used, namely journal articles and other reading materials. The data analysis techniques used are data reduction, data display and conclusion drawn. The results of this research can be concluded that punishment and reward in the perspective of the Qur'an are part of the divine justice system that aims to uphold truth and balance. In the Qur'an, it is explained that punishment is given as a reward for wrongdoing or violating Allah's commands. This punishment can be in the form of this world, such as the punishment handed down to the previous ummah or in the hereafter, which includes torture in hell. On the other hand, the Qur'an also promises rewards for those who believe and do righteous deeds. Rewards can be in the form of favors in this world or in the hereafter, with the culmination being a paradise full of pleasure. Thus, there is relevance to Education and Morality in the Modern Era It is known that the application of these concepts can help create a conducive learning environment and support character building